Budaya: Sumber Kekuatan Sekaligus Kelemahan Organisasi - Achmad Sobirin (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2002)
No longer after apprearing in Administrative Science Quarterly in 1979, the term